Design, fabrication and sensing applications of liquid-filled photonic crystal fibers - Cui, Ying (2016)
Photonic crystal fiber (PCF), on the basis of photonic crystal, is a novel class of optical fibers. PCF design, fabrication and its applications have become hot research areas since the emergence of the first PCF, which was successfully fabricated in 1996, due to its unique structures, versatile designs, excellent properties and promising performance. PCF finds a lot of applications in many areas such as fiber sensors, optical communication, fiber lasers, fiber devices and so on. Among these applications, PCF sensor, especially liquid-filled PCF sensor, is one of the most productive areas. In this thesis, a new type of PCF, namely side- channel PCF, is specially designed for liquid-filled applications. Then, this side- channel PCF is fabricated and demonstrated for liquid-filled sensing applications. This thesis first reviewed the principle and catalogs of PCFs as background knowledge. Then, various fabrication techniques of PCF are compared. Lastly, sensing applications, especially the liquid sensing applications of PCF are discussed as the preparation for the following work. After discussing the advantages and challenges of PCF serving as the liquid sensing platform, we propose a new type of PCF, i.e. side-channel PCF. This PCF has a big side-channel, which can facilitate the liquid infiltrating process. The side- channel PCF is designed and simulated with finite element method (FEM) in COMSOL Multiphysics. Then, this PCF is fabricated with stack-and-draw process. After fabrication, the characterization of this PCF is also carried out including cross-section investigation, transmission loss, bending loss, birefringence properties and so on. v ￼￼7) Abstract ￼In order to apply this side-channel PCF to sensing, suitable sensing configurations are needed. The Sagnac interferometric configuration is detailedly studied as a potential candidate. First, a strain sensing experiment is carried out by using a commercial polarization maintaining photonic crystal fiber (PM-PCF) inside the Sagnac interferometer. Through this experiment, we verify the dependence of the sensitivity of the Sagnac interferometer on sensing length and total length of the PM-PCF inside the Sagnac loop. The theoretical analysis is well supported by the experimental results. Subsequently, taking advantage of these conclusions, we carry out a temperature sensing investigation, which is a refractive index sensor in nature, by using selectively-filled PM-PCF inside Sagnac interferometric configuration. The achieved temperature sensitivity is 2.58 nm/°C, which is better than the reported results. After investigating the Sagnac configuration with commercial PM-PCF, we demonstrate two refractive index sensors with our fabricated side-channel PCF. One sensor is based on Mach-Zehnder interferometric configuration and in the form of temperature sensing. The achieved sensitivity is 8.26 nm/°C, which is better than the best result in the literature. The corresponding refractive index sensitivity is 20443 nm/RIU. The other one is based on Sagnac interferometer. This sensor relies on the birefringence property of the liquid-filled side-channel PCF. The achieved sensitivity is 0.26 nm/°C and its according refractive index sensitivity is 644.75nm/RIU. These two refractive index sensors demonstrate that our proposed side-channel PCF can work very well for the liquid-filled applications.